REGULASI DIRI ANAK PENGHAFAL AL-QUR’AN - Pangatin, Sri; Merdekasari, Arih (Jurnal Studia Insania, 2020)
This study aims to understand the self-regulation of children memorizing the Qur'an in MI Darul Ulum. Self Regulation of children memorizing the Qur'an is the ability of children to organize themselves in intrapersonal, interpersonal, and met personal aspects to become memorizers of the Qur'an. This research uses a phenomenological qualitative approach. The study subjects were three children who memorized Al-Qur'an at MI Darul Ulum Ngawi, who was 9-12 years old and had the highest memorization at MI Darul Ulum Ngawi. This study found that self-regulation in children memorizing the Qur'an (a)Intrapersonal self-regulation intrapersonal, related to the development of motivation, setting targets for memorization, The achievement of memorization quality, and effective control (b) interpersonal self-regulation, related to parenting, giving gift or punishment from parents. Impersonation of the Qur'an memorizing figure, the ability to choose the right actions in response to a friend's behavior. The ability to understand the direction of the teacher. (c) meta personal self-regulation related to the desire to maintain intentions and draw closer to Allah SWT.